Granulocyte colony-stimulating factor and stromal cell-derived factor-1 combination therapy: A more effective treatment for cerebral ischemic stroke. Issue 7 (October 2020) - Wang, Ming-Li; Zhang, Li-Xiang; Wei, Jun-Jie; Li, Lv-Li; Zhong, Wei-Zhang; Lin, Xin-Jing; Zheng, Jin-ou; Li, Xiao-Feng
Background: Drugs that promote angiogenesis include statins, recombinant human granulocyte colony-stimulating factor, and stromal cell-derived factor-1. Low doses of atorvastatin could significantly increase the vascular expressions of endothelial growth factor, and the number of peripheral blood endothelial progenitor cells (EPCs), thus improving angiogenesis and local blood flow. G-CSF is an EPC-mobilization agent used in ischemia studies for targeting angiogenesis after cerebral ischemia via EPCs. In previous clinical trials, consistent conclusions have not been reached about the effectiveness of G-CSF on ischemic stroke. Therefore, the therapeutic effect of G-CSF and its combination with other medicines need further experimental verification. It is known that atorvastatin, rhG-CSF, and SDF-1 are considered the most promising neuroprotective candidates, but a comprehensive comparison of their effects is lacking. Aims: To compare the effects of atorvastatin, stromal cell-derived factor-1, and recombinant human granulocyte colony-stimulating factor on ischemic stroke. Methods: Adult male Sprague-Dawley rats were randomly allocated to three groups: normal, sham-operated, and middle cerebral artery occlusion operated. Middle cerebral artery occlusion operated rats were further allocated into saline, atorvastatin, recombinant human granulocyte colony-stimulating factor, and recombinant human granulocyte colony-stimulating factor + stromal cell-derived factor-1 groups. Neurological function evaluation, cerebral infarction and the blood–brain barrier integrity analysis, identification of angiogenic factors, assessment of angiogenesis, expression of growth-associated protein-43, neuroglobin, glial cell-derived neurotrophic factor, and cleaved caspase 3, were performed. Results: Compared with atorvastatin or recombinant human granulocyte colony-stimulating factor alone, recombinant human granulocyte colony-stimulating factor + stromal cell-derived factor-1 treatment improved neurological performance, reduced cerebral infarction and blood–brain barrier disruption after stroke, and increased the content of stromal cell-derived factor-1, vascular endothelial growth factor, monocyte chemotactic protein 1, and basic fibroblast growth factor in peripheral blood. In addition, recombinant human granulocyte colony-stimulating factor + stromal cell-derived factor-1 promoted greater angiogenesis than atorvastatin or recombinant human granulocyte colony-stimulating factor alone and increased the expression of growth-associated protein-43, neuroglobin, and glial cell-derived neurotrophic factor, while decreasing the levels of cleaved caspase 3 in the brain after ischemic stroke. Conclusions: Combination therapy with recombinant human granulocyte colony-stimulating factor and stromal cell-derived factor-1 is more effective than atorvastatin or recombinant human granulocyte colony-stimulating factor alone in protecting against stroke-induced damage and could be an optimal therapeutic strategy for stroke.